If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2 = -3 Reorder the terms: -2 + 7x = -3 Solving -2 + 7x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 7x = -3 + 2 Combine like terms: -2 + 2 = 0 0 + 7x = -3 + 2 7x = -3 + 2 Combine like terms: -3 + 2 = -1 7x = -1 Divide each side by '7'. x = -0.1428571429 Simplifying x = -0.1428571429
| 20z^2-8zx-45zx+18x*2=0 | | 10c-2=7c+4 | | y=7x^2+16x+4 | | 2(4-3t)-(-3)+2t= | | 8=8h+24 | | 2(3x+5)+x=-5x+9 | | (n)+(n+1)+(n+3)+(n+5)=216 | | 7x+2=-3 | | 3b^2-2b=8 | | -4b(1-9b-2b^2)= | | 9.7m+6.2-12.5m=-8.9-2.8+15.1 | | 2x^2=-12x-16 | | (n)+(n+1)+(n+2)=126 | | 1=15n | | 16=(2x+1)-3 | | 9.7m+6.2-12.5m=-8.9-2.8m+15.1 | | 2m^2(2m^2+3m-5)= | | 9.7m+6.2-12.5m=-8.9-2.8m | | 2x-1-8(-12x+12)=x-9 | | 0.3m-8.4=1.5m | | 8(2f-3)=-4(4f-8) | | 2x+2+x+1=60 | | 18d=-2 | | x-3+4=a | | 38-(3c+4)=2(c+5)+c | | 3p-8=2p+12 | | 2n+3(n-1)= | | 3x^2-13y=30 | | -3n(-5n-2)-3n^2= | | -7(6-6v)=3(v-1) | | -6x+10+x=226 | | 2(x-6)+8=4x-2 |